An optimized non-destructive protocol for testing mechanical properties in decellularized rabbit trachea. (15th September 2017) - Den Hondt, M.; Vanaudenaerde, B.M.; Maughan, E.F.; Butler, C.R.; Crowley, C.; Verbeken, E.K.; Verleden, S.E.; Vranckx, J.J.
Graphical abstract: Abstract: Successful tissue-engineered tracheal transplantation relies on the use of non-immunogenic constructs, which can vascularize rapidly, support epithelial growth, and retain mechanical properties to that of native trachea. Current strategies to assess mechanical properties fail to evaluate the trachea to its physiological limits, and lead to irreversible destruction of the construct. Our aim was to develop and evaluate a novel non-destructive method for biomechanical testing of tracheae in a rabbit decellularization model. To validate the performance of this method, we simultaneously analyzed quantitative and qualitative graft changes in response to decellularization, as well as in vivo biocompatibility of implanted scaffolds. Rabbit tracheae underwent two, four and eight cycles of detergent-enzymatic decellularization. Biomechanical properties were analyzed by calculating luminal volume of progressively inflated and deflated tracheae with microCT. DNA, glycosaminoglycan and collagen contents were compared to native trachea. Scaffolds were prelaminated in vivo . Native, two- and four-cycle tracheae showed equal mechanical properties. Collapsibility of eight-cycle tracheae was significantly increased from −40 cm H2 O (−3.9 kPa). Implantation of two- and four-cycle decellularized scaffolds resulted in favorable flap-ingrowth; eight-cycle tracheae showed inadequate integration. We showed a more limited detergent-enzymatic decellularization successfully removing non-cartilaginous immunogenic matter without compromising extracellular matrix content or mechanical stability. With progressive cycles of decellularization, important loss of functional integrity was detected upon mechanical testing and in vivo implantation. This instability was not revealed by conventional quantitative nor qualitative architectural analyses. These experiments suggest that non-destructive, functional evaluation, e.g. by microCT, may serve as an important tool for mechanical screening of scaffolds before clinical implementation. Statement of Significance: Decellularization is a front-running strategy to generate scaffolds for tracheal tissue-engineering. Preservation of biomechanical properties of the trachea during this process is paramount to successful clinical transplantation. In this paper, we evaluated a novel method for biomechanical testing of decellularized trachea. We detected important loss of functional integrity with progressive cycles of decellularization. This instability was not revealed by our quantitative nor qualitative analyses. These experiments suggest that the technique might serve as a performant, non-destructive tool for mechanical screening of scaffolds before clinical implementation.